Librarian’s Perception on Marketing of Information Resources and Services in Academic Libraries with Special Reference to Amhara Region, Ethiopia - Ramadevi, Dr. V. (International Journal of Scientific Research and Management (IJSRM), 2018)
In the present scenario, information and communication technology plays a very important role. Due to the development of technology, internet has brought out some of the opportunities and challenges which provide the effective way of use the library information resources and services. Users can access the required information online irrespective of visiting the place and collecting the information as like ancient days. To improve some of the problems of information and communication technology resulting in underutilization of academic libraries, effort directed to promoting and creating awareness of library services is very important. Library staff can promote the use of the library through other means such as marketing of library services to its users. The role of academic libraries and information centres is to provide necessary information. The objectives of the study were why libraries should market their information resources and services; ways in which libraries market their information resources and services also impacts of marketing information resources and services in the academic Library. The study target population was 120 which comprised of library staff members. The study sample consisted to twenty members of the target group.